2019
DOI: 10.9734/acri/2019/v16i230085
|View full text |Cite
|
Sign up to set email alerts
|

Golden Camellias: A Review

Abstract: Golden camellias or yellow camellias are species belonging to genus Camellia L., family Theaceae. Fifty two species were described in southern China and Vietnam. Active ingredients such as polysaccharides, polyphenols, saponins, and flavonoids are well known characteristics of golden camellias. Its leaves and flowers have been long traditionally used for health improvement. It was found to be able to inhibit transplanted cancer, lower blood pressure, lower blood lipid, lower cholesterol, and prevent atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The yellow tea, Camellia sp., is a shrub and small tree belonging to the family Theaceae (Xu et al, 2018). Approximately 52 species of yellow Camellia have been described in southern China and Vietnam, of which nearly 40 species are naturally distributed in Vietnam (Manh et al, 2019;Huang et al, 2013). These plants are shade-tolerant species that grow well only in the shade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The yellow tea, Camellia sp., is a shrub and small tree belonging to the family Theaceae (Xu et al, 2018). Approximately 52 species of yellow Camellia have been described in southern China and Vietnam, of which nearly 40 species are naturally distributed in Vietnam (Manh et al, 2019;Huang et al, 2013). These plants are shade-tolerant species that grow well only in the shade.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research has shown that yellow Camellia products can inhibit transplant cancer, lower blood pressure, blood lipids, and cholesterol levels, and prevent atherosclerosis. Research has demonstrated that Camellia extracts possess antioxidant, with anionic superoxide and hydroxyl radical scavenging activities (Manh et al, 2019;Huang et al, 2013). Yellow Camellias, such as C. nitidissima, have been used to treat sore throats, diarrhea, high blood pressure, irregular menstruation and to prevent cancer (Mukhtar and Ahmad, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we reported the flowering induction of C. tamdaoensis, which is a rare camellia species with yellow flowers from Vietnam (Manh et al, 2019). Commonly known as golden camellias or yellow camellias, yellow-flowering camellias comprise 52 species.…”
mentioning
confidence: 94%
“…In recent years, many new species of yellow camellia have been reported from northern Vietnam and southern China (e.g. Tran and Nguyet 2005; Orel 2006; Orel and Wilson 2010, 2012; Orel et al 2012, 2013, 2014a, b; Tran et al 2012; Tran and Luong 2013; Huang et al 2014; Orel and Curry 2015; Tran and Le 2015; Luu et al 2015; Dung et al 2016; Luong and Le 2016; Luong et al 2016a, b; Le et al 2017; Nguyen et al 2018; Liu et al 2019), increasing the total to more than 50 species (Tran et al 2019) and making northern Vietnam another center of yellow camellia diversity. Generally, yellow camellias are rare and highly endemic due to their small population, narrow distribution and excessive gathering.…”
Section: Introductionmentioning
confidence: 99%